PENGARUH INTENSITAS MENGAKSES INFORMASI DAN KUALITAS INFORMASI PARIWISATA AKUN INSTAGRAM @disparbudwonosobo TERHADAP MINAT BERKUNJUNG WISATAWAN KE KABUPATEN WONOSOBO - Hidayat Putra, Syahida Alam Gitanjali; Luqman, Yanuar; Suryanto Gono, Joyo Nur (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This research is motivated by the problem of the number of tourists in Wonosobo Regency after the Covid-19 pandemic which has not reached the target. If based on data from Badan Pusat Statistik (BPS) Kab. Wonosobo, the percentage growth in the number of tourists from the last 3 years (2021-2023) has only reached 25%. To increase the percentage of the number of tourists, the Wonosobo Regency Tourism and Culture Office is aggressively promoting Wonosobo tourism through Instagram, but the results are still not optimal. The purpose of this study was to determine the effect of the intensity of accessing information and the quality of tourism information on the Instagram account @disparbudwonsobo on tourist interest in visiting Wonosobo Regency. This research is a quantitative study with explanatory methods and non-probability sampling techniques specifically using purposive sampling methods. Data collection was carried out by distributing questionnaires to 100 respondents with the characteristics of active Instagram users aged 18-34 years, have accessed tourism information, and have never traveled to Wonosobo Regency. To analyze the data that has been collected through surveys, SPSS 25 is used. The results of this study show that the intensity of accessing information and the quality of information affect tourist interest. This finding is in line with the basic concepts of Media Dependency Theory, Computer Mediated Communication (CMC) and Information Integration Theory.